2004
DOI: 10.1079/phn2004608
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of food insecurity among low-income households in Los Angeles County

Abstract: Objectives: To assess the prevalence and identify the predictors of food insecurity among households in Los Angeles County with incomes below 300% of the federal poverty level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
71
3
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(92 citation statements)
references
References 10 publications
10
71
3
4
Order By: Relevance
“…In contrast to studies that documented a positive association between income poverty and hunger, such as in a national sample of the USA (1) , in low-income households in Los Angeles County (21) and in people living with HIV/AIDS in Canada (22) , poverty was not associated with food insecurity in our sample. However, our findings are consistent with an association between income and hunger, as the highest-income group was the least food insecure.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to studies that documented a positive association between income poverty and hunger, such as in a national sample of the USA (1) , in low-income households in Los Angeles County (21) and in people living with HIV/AIDS in Canada (22) , poverty was not associated with food insecurity in our sample. However, our findings are consistent with an association between income and hunger, as the highest-income group was the least food insecure.…”
Section: Discussioncontrasting
confidence: 99%
“…Food insecurity status was associated with selected demographic characteristics at both the individual and child level. These findings are similar to observations from other studies in developed countries (22) as well as developing countries (8)(9)(10)23,24) . Contrary to findings from studies conducted in other developing countries (8)(9)(10)23,24) , we observed no significant association between food insecurity and education.…”
Section: Discussionsupporting
confidence: 92%
“…Em relação aos fatores associados, o estudo confirmou as evidências de publicações internacionais 27 e nacionais 18,20,29,30 , que destacam o papel fundamental da renda na determinação da insegurança alimentar e de iniquidades em sua ocorrência. Portanto, as estratégias de incremento de renda em populações vulneráveis por meio do Bolsa Família e de outros benefícios so-ciais são essenciais e precisam ser mais efetivas e equânimes.…”
Section: Discussionunclassified